Pengujian Pengelasan Plat Stainless Steel JIS SS304 Menggunakan Mikro Struktur - Wilarso, Wilarso; Farhan, Muhamad; Azharul, Firmansyah; Sholih, Hilman (Creative Research in Engineering (CERIE), 2023)
Failure in the welding process will result in a drop in quality and a risk to worker safety. Small cavities were frequently detected during welding. In order to identify the origin of the damage, the goal of this study is to investigate the presence of small circular cavities that are grouped in the welding region of gas tungsten arc welding (GTAW) welding outcomes.Â The research technique involves categorizing changes in electric current on JIS SS 304 stainless steel material with a thickness of 10 mm: GTAW 80 A root (low current), 100 A Filler (mid electric current), and 120 A Capping (high current).Â Based on investigations into the use of electric current for Gas Tungsten Arc Welding (GTAW) welding and the interpretation of discontinuity in the outcomes of welding on JIS SS 304 stainless steel material, on JIS SS 304 plate material with a thickness of 10 mm. learn about the welding methods GTAW and HAZ GTAW at the point of the microstructure as components that have thermal impacts